If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(9 + 2x) = -93 (9 * -3 + 2x * -3) = -93 (-27 + -6x) = -93 Solving -27 + -6x = -93 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + -6x = -93 + 27 Combine like terms: -27 + 27 = 0 0 + -6x = -93 + 27 -6x = -93 + 27 Combine like terms: -93 + 27 = -66 -6x = -66 Divide each side by '-6'. x = 11 Simplifying x = 11
| -x*-x=-4 | | 6u-2=0 | | 6q+15p+4(6q)+8(15p)= | | 6q+15p+4(6q)+8(15)= | | (b-6)+14=100 | | -16=s+71 | | 6x-11=3x+7 | | 2+r-21=14 | | 4(2x+7)=-4 | | 2a^2+3a+6a+9= | | -7+1= | | SA=wh+lw+lh+ls | | y=mx | | 3xy+7y=4y^2-5+2x | | 4x^2-12x+10=0 | | 1+5x=-3x+41 | | 3x^5-111x^4+27x^3=0 | | 24x^2-64x-128=0 | | 4x(x+1)=0 | | 144x^2+216x+108=0 | | q+p+4q+8p= | | 3xy+5x-2=3x^2-7y | | 24x^2+136x+80=0 | | 4x^3-12x^2+10x=0 | | 3x^2-50x-17=0 | | 4y+3x=-12 | | x^2-4x-3=0 | | 36x^2+96x+64=0 | | 5=-x+2x+4 | | 5a-8=-8 | | 5(2x-4)=5(x+1) | | 8x^2-18x+7=0 |